Improving Privacy Multi-Keyword Top-K Retrieval Search Over Encrypted Cloud Data (International Journal of Engineering and Computer Science, 2018)
Cloud computing is the emerging technology, in which storage and retrieval of sensitive data information are increased in usage. The effective data access control should be done in the effective access controlled manner through which one provide an better security. The key work search retrieval over the encrypted cloud data’s are complex and tedious process which need to more concerned to improve the user friendly environment while searching for an data over an encrypted data. In this paper, for the first time, we define and solve the challenging problem of privacy-preserving multi-keyword ranked search over encrypted data in cloud computing (MRSE). We establish a set of strict privacy requirements for such a secure cloud data utilization system. Among various multikeyword semantics, we choose the efficient similarity measure of “coordinate matching”, i.e., as many matches as possible, to capture the relevance of data documents to the search query. The proposed methodology proves that the keyword search retrieval is done effectively over the encrypted cloud data’s with the consideration of privacy requirements. The experimental results prove that the our proposed methodology is better than the already existing methodologies.